1978
DOI: 10.1128/jvi.25.1.312-318.1978
|View full text |Cite
|
Sign up to set email alerts
|

Common Sequence at the 5′ Ends of the Segmented RNA Genomes of Influenza A and B Viruses

Abstract: Guanylyl-and methyltransferases, isolated from purified vaccinia virus, were used to specifically label the 5' ends of the genome RNAs of influenza A and B viruses. All eight segments were labeled with [a-32P]guanosine 5'-triphosphate or S-adenosyl[methyl-3H]methionine to form "cap" structures of the type m7G(5')pppNm-, of which unmethylated (p)ppNrepresents the original 5' end. Further analyses indicated *that m7G(5')pppAm, m7G(5')pppAmpGp, and m7G(5')pppAmpGpUp were released from total and individual labeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Replicases from other viral species can use more than one initiation mechanism. For example, the enzyme from multipartite negativestrand RNA viruses initiates genomic and the complementary antigenomic RNA replication by a de novo mechanism but uses a cap-snatched primer for mRNA transcription (Hay et al, 1982;Honda et al, 1998;Moss et al, 1978;Young and Content, 1971). The enzymes from Nidoviruses likely initiate genomic RNA synthesis de novo, but use a discontinuous primer-dependent mechanism for subgenomic RNA synthesis.…”
Section: Figmentioning
confidence: 99%
“…Replicases from other viral species can use more than one initiation mechanism. For example, the enzyme from multipartite negativestrand RNA viruses initiates genomic and the complementary antigenomic RNA replication by a de novo mechanism but uses a cap-snatched primer for mRNA transcription (Hay et al, 1982;Honda et al, 1998;Moss et al, 1978;Young and Content, 1971). The enzymes from Nidoviruses likely initiate genomic RNA synthesis de novo, but use a discontinuous primer-dependent mechanism for subgenomic RNA synthesis.…”
Section: Figmentioning
confidence: 99%
“…To insure that the latter enzymes would be acting on the product cRNA, we designed our experiments so that any cap structure formed on the product cRNA by these enzymes would contain radioactive label derived from a precursor used in the in vitro transcription reaction. This was important because any vRNA extracted from the virus and hybridized to the product cRNA during the oligodeoxythymidylic acid-cellulose purification step would be present in the poly(A)+ cRNA preparation and would also be capped and methylated by the vaccinia virus enzymes, as the 5' end of vRNA is (p)ppA (23,29,45). The strategy we adopted was based on the assumption that cRNA synthesis primed by ApG or ppApG initiates exactly at the 3' end of vRNA.…”
Section: Resultsmentioning
confidence: 99%
“…The caps at the 5' end were evidently very similar except that the simple plus-strand plant virus caps carried only one methyl group on the external 5'-linked guanosine (type 0), while the RNA caps of the more complex viruses belonged to type 1 or 2 carrying one or two adjacent ribose-and also often base-methylated residues. A study of the uncapped ends also showed great similarities; for exam pIe, influenza viral RN As, of both types A and B, each consisting of eight components, showed the identical 5' sequence for all [(p)ppApGpUp-] (Moss et al, 1978), and the uncapped ends of all reovirus minus strands were ppGpApUp- (Furuichi et al, 1975a;Furuichi and Miura, 1975).…”
Section: Internal Sequences Of Viral Rnas and Structural Considerationsmentioning
confidence: 97%
“…The 5' and 3' end groups were found to be pppA for most if not all components (Young and Content, 1971), and -U, the latter by a method that has frequently given erroneous results (Lewandowski et al, 1971). All eight genome segments of both type A and B influenza virus start with pppA-G-U (Moss et al, 1978). In fowl plague and X31, both type A viruses, this is followed by the sequence A-G-A-A-A-U-U10-A-G-G; after a variable triplet the common sequence continues with U-U-U-U 2 °-U-U-A (Skehel and Hay, 1978a).…”
Section: Minus-strand Rna Virusesmentioning
confidence: 99%